Music as therapy in Bhim Birag’s selected songs - Shrestha, Tara Lal (Nepal Journal of Multidisciplinary Research, 2022)
An art or an artist is not beyond influences of the dominant historical- politico-cultural- forces. However, an art is a platform of meditation, where an artist can remain beyond historicity and exists as a healer. Birag lived an enduring painful physical life, but he used music as a therapy. In his simple looking serious songs he exists as a therapist, and it looks as if beyond his ideological ‘I’. In search of an escape from his painful life, he engaged his moments in composing serious songs, which embody certain level of therapeutic essence. This paper presents an outcome of the qualitative research on Bhim Birag’s biography and his selected songs primarily connecting his painful life with his creative life. On the basis of interviews and discussions along with published documents, it shows evidences about how he played some eclectic roles as a therapist persona via his celebrated songs. Finally, this research tries to connect the therapeutic essence of his serious songs to historicity from the eclective approach, where his ideological ‘I’ converses with his therapist persona and his texts (songs) negotiate to the politico-cultural contexts.